Taxonomic studies of Araceae in Myanmar I: Typhonium sagaingense, a new Areae species from Sagaing Region - Naive, Mark Arcebal K.; Hein, Khant Zaw; Ma, Zheng-Xu; Du, Nguyen Van (Phytotaxa, 2020)
A species new to science, Typhonium sagaingense from Sagaing Region, Myanmar, is herein described and illustrated. It is similar to T. albidinervum and T. filiforme but differs in having following characters: trifoliolate leaves, spadix slightly shorter than spathe, fewer yellow staminodes arranged in one whorl and pink appendix. Detailed descriptions, colour plates, illustration, distribution, phenology and ecology of the new species are provided, including a key to all Typhonium occurring in Myanmar.